The Impact of Store Brands on Overall Product Category Performance - McCollum, Joseph; Pepe, Michael (Journal of Applied Business and Economics, 2023)
A comprehensive store-level data set of 9 dairy product categories across 149 stores of a supermarket retailer chain over 32 weeks in 2021 was used to examine the impact of store brands on overall category performance as measured by net margin dollars. The study examines results on both the overall dairy department and category specific performance. The results for the overall dairy department indicate there is not a significant positive relationship between a change in overall store brand sales penetration and profitability. There is, however, a significant positive relationship between overall store brand net margin dollar penetration and category profitability.